Grape seed oil as a sustainable cutting fluid in minimum quantity lubrication (MQL) for enhanced surface roughness and corrosion resistance in 316L stainless steel face milling - Teguh Dwi Widodo; Rudianto Raharjo; Redi Bintarto; Asri Anjasari; Arif Wahyudiono; Muhammad Zaimi Bin Zainal Abidin (Universitas Muhammadiyah Magelang, 2025)
This work investigates grape seed oil as a green substitute for conventional mineral-based cutting fluids to reach sustainable manufacturing methods. The application of grape seed oil as a cutting fluid in the machining of 316L stainless steel using the MQL method has not been documented in prior research studies. In this work, the study focuses on determining the effect of the grape seed oil on the surface integrity and comparing these findings to standard dry machining conditions by examining surface topography, roughness, and corrosion resistance at three different spindle speeds (1500, 1800, and 2100 rpm). Results of experiments showed that grape seed oil greatly improved surface quality and corrosion resistance. Surface roughness dropped noticeably by 61.6% at 1500 rpm as opposed to dry machining. Likewise, changes in surface roughness noted were 54.0% at 1800 rpm and 54.9% at 2100 rpm. Furthermore, the potentiodynamic polarization data show that the grape seed oil greatly prevents post-machining corrosion of 316 L stainless steel. The corrosion rates of the material face milled using grape seed oil were decreased by 78.6%, 74.6%, and 80.8% at spindle speeds of 1500, 1800, and 2100 rpm, respectively, when compared with dry face milling. These results indicate that grape seed oil demonstrates its ability as a cutting fluid even for high-speed machining operations. Hence, grape seed oil can address industrial demands for more environmentally friendly manufacturing methods.